Clomiphene citrate, metformin or a combination of both as the first line ovulation induction drug for Asian Indian women with polycystic ovarian syndrome: A randomized controlled trial - Sujata Kar; Smriti Sanchita (Wolters Kluwer Medknow Publications, 2015)
Aim: To compare clomiphene citrate (CC), metformin or the combination of CC and metformin as the first line ovulation induction drug in Asian Indian women with polycystic ovary syndrome (PCOS). Methods: One hundred and five newly diagnosed, treatment naive PCOS women were recruited. They were randomized into any of the three groups: Group I (CC 50-150 mg/day), Group II (metformin 1700 mg/day), and Group III (CC + metformin in similar dosage to Groups I and II). Patients underwent follicular monitoring and advice on timed intercourse. The study period was 6 months, or till pregnant, or till CC resistant. Primary outcome studied was live birth rate (LBR). Secondary outcomes were ovulation rate, pregnancy rate, and early pregnancy loss rate. Results: There was no significant difference among the groups in baseline characteristics and biochemical parameters. LBR was 41.6%, 37.5%, and 28.1%, respectively in Groups III, II, and I. Group III (CC + metformin) had the highest ovulation (83.3%), pregnancy (50%), and LBRs (41.6%). Group II (metformin) was as good as Group I (CC) in all the outcomes. CC + metformin (Group III) had statistically significantly higher ovulation rate as compared to CC alone (Group I) (P = 0.03; odds ratio: 95% confidence interval: 3.888 [1.08-13.997]). Conclusion: Thus, our study shows that metformin was as good as CC in terms of "LBR" and the combination of CC and metformin gave the highest ovulation and LBR.